2021
DOI: 10.1021/jacs.1c06656
|View full text |Cite
|
Sign up to set email alerts
|

A New Solid-State Proton Conductor: The Salt Hydrate Based on Imidazolium and 12-Tungstophosphate

Abstract: We report the structure and charge transport properties of a novel solid-state proton conductor obtained by acid–base chemistry via proton transfer from 12-tungstophosphoric acid to imidazole. The resulting material (henceforth named Imid3WP) is a solid salt hydrate that, at room temperature, includes four water molecules per structural unit. To our knowledge, this is the first attempt to tune the properties of a heteropolyacid-based solid-state proton conductor by means of a mixture of water and imidazole, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 61 publications
0
48
0
Order By: Relevance
“…POMs have been regarded as versatile nanobuilding blocks and are widely employed in the fabrication of precise nanostructures, as well as functional hybrid materials . Particularly, the excellent electrochemical stability and the high ion-dissociation ability of POMs enable them as promising electrolytes to transport ions such as protons and lithium ions . Moreover, the polyanionic property allows POMs as electrostatic cross-linkers to construct ionic self-assembled materials.…”
Section: Introductionmentioning
confidence: 99%
“…POMs have been regarded as versatile nanobuilding blocks and are widely employed in the fabrication of precise nanostructures, as well as functional hybrid materials . Particularly, the excellent electrochemical stability and the high ion-dissociation ability of POMs enable them as promising electrolytes to transport ions such as protons and lithium ions . Moreover, the polyanionic property allows POMs as electrostatic cross-linkers to construct ionic self-assembled materials.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experimental results have shown that imidazole molecules generally have excellent proton conductibility and that the introduction of imidazole molecules usually causes a significant enhancement in the proton conduction of the material. ,,, Compared to bulk imidazole of 1 H SSNMR spectra (10.1 and 6.8 ppm), however, a prominent downfield shifting of the imidazole proton signal was observed in HUP-3 . This suggests that imidazole is possible for hydrogen bond interaction with the structural skeleton of HUP-3 .…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, in proton-conducting CPs/MOFs, proton conductivity may be affected by intrinsic factors such as substitution of building blocks (metal clusters, ligands, and guest molecules/ions). Therefore, the desired proton-conducting behavior of crystalline materials can be controlled through the optimization of these building blocks. However, up to now, crystalline proton-conducting materials exhibiting thermally stable, intrinsically high anhydrous proton conductivity that can be directly used as the electrolyte in a practical fuel cell assembly under a wide range of operating temperatures are still quite rare. , …”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs) are a specific family of anionic d -block metal oxide clusters with prominent redox and acidic/basic property, and have been recognized as significant catalysts for a variety of reactions, including oxidation and acid catalysis of organic substrates. Nevertheless, the application prospects of bulk POMs as catalysts are hindered by their low specific surface area and solvent solubility. This leads to poor recyclability due to the loss of active sites. , To ameliorate their stability and recyclability problems, POM-incorporated metal-organic networks provide a fruitful strategy. , POMs possess a high electronic diversity and rich structural versatility, and can hence serve as intriguing inorganic building blocks to interact with metal-organic fragments via multiple interactions including hydrogen or coordination bonds to achieve the heterogenization of POM clusters. Moreover, POM-incorporated metal-organic networks not only reserve the redox nature of POMs and integrate additional active sites from metal-organic networks, but also improve their insolubility and recyclability as heterogeneous catalysts, achieving the goal of “killing three birds with one stone”. Therefore, POM-incorporated metal-organic networks serve as potential promising heterogeneous catalyst candidates for selective oxidation of aryl alkenes to aldehydes, in which a rational structural design is pivotal.…”
Section: Introductionmentioning
confidence: 99%